Brief Intervention for Drug Abusing Adolescents in a School Setting: Outcomes and Mediating Factors - Winters, Ken C. (2011)
This randomized controlled trial evaluated the use of two brief intervention conditions for adolescents (aged 12–18 years) who have been identified in a school setting as abusing alcohol and other drugs. Adolescents and their parent (N = 315) were randomly assigned to receive either a 2-session adolescent only (BI-A), 2-session adolescent and additional parent session (BI-AP), or assessment only control condition (CON). Interventions were manually guided and delivered in a school setting by trained counselors. Adolescents and parents were assessed at intake and at 6 months following the completion of the intervention. Analyses of relative (change from intake to 6-months) and absolute (status at 6-months) outcome variables indicated that for the most part, adolescents in the BI-A and BI-AP conditions showed significantly more reductions in drug use behaviors compared to the CON group. Also, youth receiving the BI-AP condition showed significantly better outcomes compared to the BI-A group on several variables. Problem-solving skills and utilization of additional counseling services mediated outcome. The value of a school-based brief intervention for students is discussed.